Bioengineering of Dental Tissues: Bibliometric Analysis 2000-2011. - Sebastián Zamorano; Lissete Guzmán; Flavio Zamorano (Universidad de Concepción., 2014)
Introduction: There has been a noticeable increase in experimental use and therapies based on stem cells over recent years. Nevertheless, there is a lack of information about this progress in the dental field, which makes it difficult to trace development and design policies. The purpose of this study, as a first approach to the subject, is to determine a bibliometric profile for the investigation related to bioengineering of dental tissue at a worldwide scale, based on the MEDLINE database, for the period 2000-2011. Methodology: A bibliometric study was carried out. Every article indexed in the MEDLINE database and associated with the terms "stem cells" and "tooth regeneration" for the period 2000-2011 was included. The analyzed variables were publishing date, country of origin, language and publication type (original or review), journal, author, associated university and tissue source (human or animal). Results: For the entire period included in the study, 257 articles were found. Of these, 149 corresponded to original Works published in English; 5 in other languages; 92 comprised literature reviews in English, 9 in other languages and 2 publications were included in the "others" category. The countries with the highest research productivity were the United States (24.51%), Japan (20.62%) and China (17.90%), while Brazil (3.9%) was the only Latin-American country found in the list. Animal tissues were used in 59.09% of them. The most productive authors were Ueda M (17) and Jin Y (11), whereas Fourth Military University (13), University of Tokyo (12) and Capital Medical University (10) had the largest number of publications. Conclusion: The United States, Japan and China concentrate about two thirds of the production. Latin-America was represented only by Brazil.